Impact of Social Work Characteristics on Turnover Intention of Millennials - SEBASTIAN, BIJU; VIRANI, DR. FARIDA (The journal of contemporary issues in business and government, 2021)
Organizations are still grappling to understand the nuances of working of millennials so that HRM practices can be upgraded to handle their attraction and retention more effectively. There is an increased interest among practitioners and scholars to understand the impact of social work characteristics on various employee lifecycle touch points in order to make organizations more appealing to young employees. This study aims to empirically test the impact of social work characteristic on turnover intentions of millennials. The study was conducted in a manufacturing company which has various production facilities and sales branches across India with a sample size of 268 respondents. The study uses four social work characteristics – (i) Social support, (ii) Interdependence, (iii) Interaction outside the organization (iv) Feedback from others as antecedent constructs on turnover intention of millennials which is the out-come construct. The findings of the study are consistent with the results of previous researches with significant managerial implications